Natural Cytotoxicity Receptors: Broader Expression Patterns and Functions in Innate and Adaptive Immune Cells - Hudspeth, Kelly; Silva-Santos, Bruno; Mavilio, Domenico (Frontiers in Immunology, 2013)
Natural cytotoxicity receptors (NCRs) have been classically defined as activating receptors delivering potent signals to Natural Killer (NK) cells in order to lyze harmful cells and to produce inflammatory cytokines. Indeed, the elicitation of NK cell effector functions after engagement of NCRs with their ligands on tumor or virus infected cells without the need for prior antigen recognition is one of the main mechanisms that allow a rapid clearance of target cells. The three known NCRs, NKp46, NKp44, and NKp30, comprise a family of germ-line encoded Ig-like trans-membrane (TM) receptors. Until recently, NCRs were thought to be NK cell specific surface molecules, thus making it possible to easily distinguish NK cells from phenotypically similar cell types. Moreover, it has also been found that the surface expression of NKp46 is conserved on NK cells across mammalian species. This discovery allowed for the use of NKp46 as a reliable marker to identify NK cells in different animal models, a comparison that was not possible before due to the lack of a common and comprehensive receptor repertoire between different species. However, several studies over the recent few years indicated that NCR expression is not exclusively confined to NK cells, but is also present on populations of T as well as of NK-like lymphocytes. These insights raised the hypothesis that the induced expression of NCRs on certain T cell subsets is governed by defined mechanisms involving the engagement of the T cell receptor (TCR) and the action of pro-inflammatory cytokines. In turn, the acquisition of NCRs by T cell subsets is also associated with a functional independence of these Ig-like TM receptors from TCR signaling. Here, we review these novel findings with respect to NCR-mediated functions of NK cells and we also discuss the functional consequences of NCR expression on non-NK cells, with a particular focus on the T cell compartment.